THE CULTURE OF THE TOBA BATAK FAMILY IN NGERI-NGERI SEDAP FILM: CHARLES SANDERS PEIRCE'S SEMIOTICS ANALYSIS - Dewi K. Soedarsono (INFOKUM, 2022)
Indonesia is one of the countries with a large island, which means that the population of Indonesia is diverse, with the population consisting of various religions, tribes, languages, races and cultures. As time goes by and in line with the times, there are more and more ways to introduce and know every culture in Indonesia. Mass media is one of the introductory references and ways to get to know more about various cultures in Indonesia, one of the media that people like is film. Film is one of the channels in conveying the message and meaning of culture to the audience, because films can reach people in large numbers and also quickly. One of the films in which there is a cultural meaning is the film “Ngeri-Ngeri Sedap”. This film consists of the cultural meaning of the Batak Toba family in the form of visual images and audio. Thus, this study aims to explain the various cultural meanings contained in the film Horror-Horrified Sedap, and how each of these meanings is interpreted. The research method used is qualitative research with a descriptive type of research. The approach used is semiotic analysis using Charles Sanders Peirce's semiotic model which focuses on significant signs. The data obtained is the data of each piece of the scene divided into several units of analysis. As a result, 15 scenes were found in the form of visual images and audio visuals containing the cultural meaning of the Batak Toba family, which have different meanings. It is also found that unique and interesting things from each scene exist, through interviews conducted.